Analisis Perlakuan Akuntansi Penjualan Konsinyasi pada Minimarket S_Mart Kuala Tungkal - Baining, Mellya Embun; Faturahman, Faturahman; Sari Usda, Fitri Nadia (Lembaga Yasin AlSys, 2025)
This research is motivated by the importance of accuracy in recording consignment sales transactions which are still an obstacle for retail businesses, especially at Minimarket S_Mart Kuala Tungkal. Lack of understanding of proper accounting treatment causes financial information not to be presented reliably, thus affecting the decision-making process. This study aims to analyze the accounting treatment of consignment sales and assess its conformity with financial accounting standards. The research used a qualitative approach with a case study method. Data collection techniques include observation, in-depth interviews, and documentation, with the research subjects consisting of shop owners, treasurers, and transaction and bookkeeping documents. Data analysis was carried out descriptively qualitatively through the stages of reduction, presentation, and conclusion drawing.The results showed that Toko S_Mart applies the non-separate recording method in reporting consignment sales and regular sales, which is considered to facilitate daily operations but limit the accuracy of detailed profit analysis. In addition, inconsistencies were found in revenue recognition and recording transactions that were not fully in accordance with accrual accounting principles. In conclusion, although recording practices reflect a basic understanding of consignment transactions, there is a need to improve technical rigor and the use of more detailed recording methods in order to produce financial statements that are relevant, reliable and useful to management in making decisions.